Liver iron content determination by magnetic resonance imaging - Tziomalos, Konstantinos (The WJG Press and Baishideng, 2010)
Accurate evaluation of iron overload is necessary to establish the diagnosis of hemochromatosis and guide chelation treatment in transfusion-dependent anemia. The liver is the primary site for iron storage in patients with hemochromatosis or transfusion-dependent anemia, therefore, liver iron concentration (LIC) accurately reflects total body iron stores. In the past 20 years, magnetic resonance imaging (MRI) has emerged as a promising method for measuring LIC in a variety of diseases. We review the potential role of MRI in LIC determination in the most important disorders that are characterized by iron overload, that is, thalassemia major, other hemoglobinopathies, acquired anemia, and hemochromatosis. Most studies have been performed in thalassemia major and MRI is currently a widely accepted method for guiding chelation treatment in these patients. However, the lack of correlation between liver and cardiac iron stores suggests that both organs should be evaluated with MRI, since cardiac disease is the leading cause of death in this population. It is also unclear which MRI method is the most accurate since there are no large studies that have directly compared the different available techniques. The role of MRI in the era of genetic diagnosis of hemochromatosis is also debated, whereas data on the accuracy of the method in other hematological and liver diseases are rather limited. However, MRI is a fast, non-invasive and relatively accurate diagnostic tool for assessing LIC, and its use is expected to increase as the role of iron in the pathogenesis of liver disease becomes clearer.